2010
DOI: 10.3758/s13421-010-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

Rich in vitamin C or just a convenient snack? Multiple-category reasoning with cross-classified foods

Abstract: Two studies examined multiple category reasoning in property induction with cross-classified foods. Pilot tests identified foods that were more typical of a taxonomic category (e.g., "fruit"; termed 'taxonomic primary') or a script based category (e.g., "snack foods"; termed 'script primary'). They also confirmed that taxonomic categories were perceived as more coherent than script categories. In Experiment 1 participants completed an induction task in which information from multiple categories could be search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…When they were asked to decide the level of amino acids in apples (which are both a fruit and a snack), they showed evidence of using the levels in both categories to produce an answer. The results of Murphy and Ross point out that multiple categories of an item can in some circumstances be simultaneously taken into account and coordinated (see also Hayes, Kurniawan, & Newell, 2011). Therefore, young children must eventually learn not to decide whether an item belongs to one category or the other, but to take both categories into account in making an accurate induction.…”
Section: Discussionmentioning
confidence: 98%
“…When they were asked to decide the level of amino acids in apples (which are both a fruit and a snack), they showed evidence of using the levels in both categories to produce an answer. The results of Murphy and Ross point out that multiple categories of an item can in some circumstances be simultaneously taken into account and coordinated (see also Hayes, Kurniawan, & Newell, 2011). Therefore, young children must eventually learn not to decide whether an item belongs to one category or the other, but to take both categories into account in making an accurate induction.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has shown that people often show a single-category focus when making inductions about cross-classified items (Murphy & Ross, 1999), and it has been suggested that the activation of one category inhibits activation of other possible categories (Macrae, Bodenhausen, & Milne, 1995). As when reasoning with uncertain categories, people are able to use category information normatively when making inferences about a cross-classified item (Hayes, Kurniawan, & Newell, 2011), but they often do not. The distinction between implicit and explicit processes may also be useful in characterizing situations when people use category information more normatively.…”
Section: Discussionmentioning
confidence: 99%
“…Category coherence refers to the extent to which category exemplars and/or features are seen to go together in light of theoretical or causal knowledge (Murphy & Medin, 1985). Members of coherent categories typically show high levels of similarity to one another (Haslam, Rothschild, & Ernst, 2000), and people are more likely to generalize a property from a high-coherence category than from a low-coherence category to a new member (e.g., Hayes, Kurniawan, & Newell, 2011; Patalano & Ross, 2007; Rehder & Hastie, 2004).…”
Section: Category Coherencementioning
confidence: 99%